Pengaruh Model Pembelajaran Flipped Classroom Terhadap Hasil Belajar Siswa Pada Materi Laju Reaksi Di SMA Katolik Karitas Tomohon - Pasere, Elsi; Lumingkewas, Sonny (Chemistry Department, Universitas Negeri Manado, 2025)
This study was conducted to determine the effect of the flipped classroom learning model on student learning outcomes in the reaction rate material at Karitas Catholic High School, Tomohon. This study used a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of two classes. namely the experimental class which was given treatment using the flipped classroom learning model and the control class which used the direct learning model. The instrument used was a multiple-choice test in the form of a pretest and posttest of 20 questions. The results showed that the average value of the experimental class was 77.29 which was higher than the control class with an average of 69.58 which was continued with a t-test assisted by the SPSS 27 application, obtained a significant level value of 0.002 <α (0.05). In addition, the N-Gain test showed that the average increase in learning outcomes in the experimental class reached 78.14% and was included in the high category. Therefore, this study shows a significant influence and improvement on student learning outcomes by using the flipped classroom learning model on reaction rate material at Karitas Catholic High School, Tomohon, compared to direct learning methods.